Deamidation-related blood biomarkers show promise for early diagnostics of neurodegeneration - Jijing Wang; Ya-Ru Zhang; Xue-Ning Shen; Jinming Han; Mei Cui; Lan Tan; Qiang Dong; Roman A. Zubarev; Jin-Tai Yu (BMC, 2022)
Abstract Background The strongest risk factor of neurodegenerative diseases (NDDs) is aging. Spontaneous asparaginyl deamidation leading to formation of isoaspartate (isoAsp) has been correlated with protein aggregation in NDDs. Methods Two cohorts consisting of 140 subjects were studied. Cohort 1 contained patients with AD and healthy controls, while Cohort 2 recruited subjects with mild cognitive impairment (MCI), vascular dementia (VaD), frontotemporal dementia (FTD), Parkinson's disease (PD) and healthy controls. The levels of isoAsp in plasma human albumin (HSA), the most abundant protein in plasma, as well as the levels of immunoglobulin G (IgG) specific against deamidated HSA were measured. Apart from the memory tests, plasma biomarkers for NDDs reported in literature were also quantified, including amyloid beta (Aβ) peptides Aβ40 and Aβ42, neurofilament light protein (NfL), glial fibrillary acidic protein (GFAP) and phosphorylated tau 181 (p-tau181) protein. Results Deamidation products of blood albumin were significantly elevated in vascular dementia and frontotemporal dementia (P < 0.05), but less so in PD. Intriguingly, the deamidation levels were significantly (P < 0.01) associated with the memory test scores for all tested subjects. Deamidation biomarkers performed superiorly (accuracy up to 92%) compared with blood biomarkers Aß42/Aß40, NfL, GFAP and p-tau181 in separating mild cognitive impairment from healthy controls. Conclusion We demonstrated the diagnostic capacity of deamidation-related biomarkers in predicting NDDs at the early stage of disease, and the biomarker levels significantly correlated with cognitive decline, strongly supporting the role of deamidation in triggering neurodegeneration and early stages of disease development. Prospective longitudinal studies with a longer observation period and larger cohorts should provide a more detailed picture of the deamidation role in NDD progression.